Evolutionary trade-off in reproduction of Cambrian arthropods - Ou, Qiang (Sci Adv, 2020)
Trade-offs play a crucial role in the evolution of life-history strategies of extant organisms by shaping traits such as growth pattern, reproductive investment, and lifespan. One important trade-off is between offspring number and energy (nutrition, parental care, etc.) allocated to individual offspring. Exceptional Cambrian fossils allowed us to trace the earliest evidence of trade-offs in arthropod reproduction. †Chuandianella ovata, from the early Cambrian Chengjiang biota of China, brooded numerous (≤100 per clutch), small (Ø, ~0.5 mm) eggs under carapace flaps. The closely related †Waptia fieldensis, from the middle Cambrian Burgess Shale of Canada, also brooded young, but carried fewer (≤ 26 per clutch), larger (Ø, ~2.0 mm) eggs. The notable differences in clutch/egg sizes between these two species suggest an evolutionary trade-off between quantity and quality of offspring. The shift toward fewer, larger eggs might be an adaptive response to marine ecosystem changes through the early-middle Cambrian. We hypothesize that reproductive trade-offs might have facilitated the evolutionary success of early arthropods.